Perkembangan Sektor Pertanian Dengan Implementasi Akad Mudharabah Di Desa Arok Kecamatan Burneh Kabupaten Bangkalan - Abdul Wahid; Achmad Junaidi; Ulya Dharojah (Ta'amul: Journal of Islamic Economics, 2026)
The agricultural sector is a crucial macroeconomic pillar; however, financing stagnation frequently occurs due to the rigid fund allocation of formal institutions. Islamic economics offers profit-sharing schemes as a solution. This study analyzes the operational mechanism of informal mudharabah contracts in Arok Village, Bangkalan Regency, its impact on farmers' welfare, and its supporting and inhibiting factors. Utilizing a qualitative phenomenological approach, primary data were collected through in-depth interviews with 12 key informants (mudharib, shahibul maal, and community leaders) from October 2025 to April 2026. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. Results indicate that mudharabah operates in an informal-communitarian realm via oral contracts without physical collateral. Risks from absent written documents are adaptively mitigated through local social capital—specifically asymmetric trust and communal sanctions to suppress moral hazard. This partnership enhances farmers' economic and spiritual welfare through fair income distribution and freedom from middlemen. However, sustainability remains hindered by limited local investor capital and low Islamic accounting literacy among farmers. Scientifically, this study contributes by reconstructing a social capital-based agrarian risk mitigation model as a substitute for material collateral. Institutional reconstruction via synergy with Farmers' Waqf Banks or Islamic cooperatives is recommended.